Faktor Penyebab Kecemasan Peserta Didik dalam Menghadapi Ujian Nasional di SMP Negeri 1 Sasak Ranah Pasisie Kabupaten Pasaman Barat - Musnika, Yulia; Kasih, Fitria; Nita, Rahma Wira (Bimbingan dan Konseling, 2013)
Â This study aimed to describe the factors that cause anxiety learners in the national exams in SMP Negeri 1 Sasak Ranah Pasisie West Pasaman. This type of research is a descriptive study sought to describe a phenomenon, fact, event or occurrence that is going on. The population in this study was students at SMP Negeri 1 Sasak Ranah Pasisie West Pasaman IX class consisting of three classes with the number 109. In this study the samples were taken by using purposive random sampling technique, this sampling technique based on considerations specific or particular purpose, of the total population three so that the sample obtained by totaling 52 learners are IX1 class, IX2 and IX3. The instrument used in this study was a questionnaire compiled by the scale, while the techniques for data analysis using techniques percentage of the result in sentences that are grouped into five categories, namely: a little much, much, pretty much, and a lot less. The research results revealed that: 1) factors that cause of anxiety learners in the national exams in SMP Negeri 1 Sasak Ranah Pasisie seen domains of cognitive factors including the many categories. 2) factors that cause students anxiety in the face of national exams in SMP Negeri 1 Sasak Ranah Pasisie seen of biological factors including the many categories. Based on the study results, the authors suggest that more students prepare for the national exams, with an insight and knowledge of learners and mental preparation for the national exams.Â